PW 1242 Effects of acute symptoms and level of rest on symptom duration among youth with sports-related concussions. (November 2018) - Yang, Jingzhen; Singichetti, Bhavna; Huang, Lihong; Newton, Alison; Pommering, Thomas; MacDonald, James; Tiso, Michael; Xun, Pengcheng; Yeates, Keith O
Abstract : The 2017 Berlin Consensus on sport-related concussion (SRC) recognized the potential benefits of a gradual return-to-activity as early as immediately after the acute phase (24–48 hours after injury) as part of early clinical management. However, the optimal level of rest needed to promote recovery remains unknown. This study aimed to objectively measure physical activity during the first week post-injury among youth with SRC, and to examine the associations of acute symptoms, level of rest and symptom duration. Youth athletes ages 11 to 17 were recruited pre-injury and enrolled within 72 hours following a physician-diagnosed concussion. Injury information and acute clinical presentation were assessed at the time of injury. Participants were prospectively followed at day 7 and at symptom resolution (or a maximum of 45 days post-concussion) to assess post-concussion outcomes. Participating youth were also monitored on daily physical rest using Actigraphs, and post-concussive symptoms using daily surveys. Findings show that a total of 44 concussed youth athletes were included, with a majority being 13–16 years old (79.5%), males (68.2%), and injured in American football (43.2%). The average symptom score at injury was 39.5 and average symptom duration was 17 days. Higher acute symptom scores were significantly correlated with longer symptom duration (r=0.45, p=0.0148). Specifically, athletes with symptom duration >14 days had higher average acute symptom score (p=0.0083), and scores remained consistently high post-injury than those with symptom duration ≤14 days. While an increased trend in physical activity (representing a decrease in rest) from enrollment to day 7 post-injury was recorded by Actigraphs for both groups, athletes with symptom duration ≤14 days, on average, engaged in more steps each day than their counterparts. Inconclusion, our findings provide additional evidence for informing treatment decisions about optimal rest/activity and current return-to-play guidelines for SRC among youth athletes.